THE AUTONOMOUS RIGHT TO EVIDENCE AND ITS EARLY PRODUCTION IN BRAZILIAN CIVIL PROCEDURE LAW (REMUNOM, 2024)
This article explores the autonomous right to evidence and pre-trial “discovery” in the Brazilian civil procedure. Initially, it discusses the legal foundations of the autonomous right to evidence, as established by Article 381 of the Brazilian Civil Procedure Code (2015), emphasizing its significance in ensuring effectiveness and fairness in litigation management. Subsequently, it analyzes the legislative evolution of pre-trial “discovery” in Brazil, from its origins to the significant amendments introduced by the 2015 Code of Civil Procedure, which streamlined access to essential evidence for efficient judicial proceedings. The economic impacts of these practices are examined, revealing benefits such as reduced procedural costs, alleviation of judicial workload, and promotion of consensual conflict resolution. Moreover, pre-trial “discovery” is regarded as a crucial tool for enhancing procedural efficiency, enabling quicker and more effective responses to judicial demands. In conclusion, strengthening and expanding the autonomous right to evidence and pre-trial “discovery” are pivotal for modernizing the Brazilian judicial system. These practices not only enhance access to justice but also bolster confidence in the legal system's capacity to resolve disputes equitably and effectively.